Assembling a Biosocial Actor-Network: The Association of Relatives of Psychiatric Patients (Afaps) in Chilean Mental Health Policies - Toro-Leyton, J (UNIV REPUBLICA, FAC PSICOLOGIA, 2019)
The present article seeks to understand the socio-material practices that produced the emergence of the Association of Relatives of Psychiatric Patients (AFAPs) in contiguity with the transformations of Chilean public mental health policies. In this sense, at first the changes in the regulatory regulations of mental health policies are contextualized until the adoption of the community perspective, to then discuss from the concepts of Biological/Neurochemical Citizenship and Biosociality the analytical possibilities they provide to understand the specificity of social activism in mental health. Methodologically, some analytical tools of the actor-network theory (ANT) are presented, as they allowed us to approach the network of socio-material practices that made possible the emergence of the Association. Finally, four assemblages identified during the investigation are described and conclusions are presented associated with characterizing the activism deployed and its political implications.